Altered metabolism in pulmonary hypertension: fuelling the fire or just smoke?. Issue 4 (9th April 2020) - Duan, Daisy; Gu, Chenjuan; Jun, Jonathan C.
Pulmonary arterial hypertension (PAH) is characterised by progressive obliteration of the pulmonary vasculature, culminating in right-sided heart failure (HF). In recent years, studies have observed an association between systemic metabolic dysfunction, PAH and right ventricular failure [1]. Patients with PAH have an increased prevalence of obesity [2] and type 2 diabetes [3, 4]. Interestingly, abnormal glucose metabolism is evident even in non-diabetic individuals with PAH [5–7], and serves as an independent predictor of prognosis [8]. Glucose and fat metabolism are altered in pulmonary arterial hypertension, but it is not yet clear if these changes are causes or effects of the disease http://bit.ly/3cWyf66